A importância da criação e transferência de conhecimento em incubadoras tecnológicas: o caso da Incubadora Tecnológica de Guarulhos - Tavares, Herida Cristina (2010)
The objective of this thesis is to analyze the process of creating and transferring knowledge in technological business incubators in view of the innovation process. Thus, to investigate what are the sources of knowledge and what level of generation and transfer of knowledge relevant to innovation in the Technology Incubator of Guarulhos. In particular, the work proposes to examine the modes of knowledge creation and transfer of intra and interincubator and the incubator environment is favorable for the creation and transfer of knowledge. The research procedure used is a literature search. For further research, a case study is also conducted by means of data collection, in which the chief administrator of each incubated company answer a semi-structured questionnaire. The results of this study, with their limited sample size, have no statistical validity to the technology incubator of Guarulhos in general. But shows that formal networks of knowledge are the sources of knowledge more relevant to the development of innovative products or processes of the incubated companies. Another conclusion is that the level of knowledge transfer is directly linked to the level of interaction between enterprises and other agents, either within or outside the incubator. So, about knowledge transfer intra-incubator was found that the level of interaction is low. In an inter-incubator is also low, with few companies having some kind of agreement for cooperation with industry, universities or research centers